PELAKSANAAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH ORANG DEWASA STUDI DI KEJAKSAAN NEGERI NIAS SELATAN - Laia, Rahmat (LPPM Universitas Nias Raya, 2025)
In criminal cases including the offender, victim, victim's family, and other connected parties, restorative justice emphasizes restoration to the pre-crime state rather than vengeance in an effort to find an equitable conclusion. The purpose of this study is to ascertain how the South Nias District Prosecutor's Office uses restorative justice to address abuse-related crimes committed by adult subjects. Sociological or empirical legal research is the kind that is employed; it looks at relevant legal provisions based on real-world events in a society. The primary, secondary, and tertiary data that were gathered from secondary legal texts were used in the data gathering process. Qualitative data analysis is the method employed. Analyzing qualitative data is done concurrently with the process of gathering data. The best option provided by the South Nias District Prosecutor's Office for resolving a crime in a family-friendly manner is the application of restorative justice in the resolution of criminal acts of abuse committed by adult students, according to the findings of research conducted in the area. Both sides gain from this settlement in terms of time, fines, and expenses. The Prosecutor will present both parties to give guidance and broker a settlement for its execution. If they consent, the prosecutor will sentence the offender in accordance with the terms of the agreement. Subsequently, both sides execute a formal agreement that serves as a legally enforceable commitment for both parties.